O ensino da Cinématica baseado no enfoque CTS: O olhar de professores da EJA - Alves, Eliane Pereira (2020)
The kinematics teaching has been marked by the mathematical formalism and the decontextualization in Science / Physics classes. Regarding to Youth and Adult Education (EJA), the challenges go beyond the content taught in the classroom. Among many possibilities of teaching Science / Physics at EJA, this work will highlight the thematic approach linked to the relationship between Science, Technology and Society (CTS). Although the Curricular Proposal for Youth and Adult Education (PCEJA) directs Science / Physics teaching to the CTS approach, according to research carried out to construct the theoretical framework, teachers teaches content in EJA in the same way as worked in regular education, but in a reduced way. Therefore, we have the assumption that EJA Science / Physics teachers do not direct the concepts of kinematics to the thematic approach related to the interactions between CTS. We propose to answer the following question: "How have EJA Science / Physics teachers related or not the concepts of kinematics to the CTS approach?". Thus, we investigated the use of the CTS approach by EJA Science / Physics teachers, analyzing the way in which teachers have related the CTS approach to the Kinematics teaching. To achieve our goal, we prepared a road map and interviewed 15 teachers from municipal and state schools in Campina Grande and surrounding cities. Of the 15 teachers interviewed, 7 do not know the term CTS and 3 stated that they use the methodological approach, only as a form of context to introduce the content. In this way, we may conclude that our hypothesis has been confirmed: Teachers do not use interactions between CTS in kinematics classes. At the end of the interviews, we identified the need for specific didactic material for EJA, so we prepared a teaching proposal with a focus on the topic in question and validated it through the application of an online questionnaire. From the teacher’s evaluation, we consider that our teaching proposal is viable to be applied in EJA.